The Impact of North Sumatra's Trade Balance on Economic Growth in North Sumatra from an Islamic Economic Perspective - Dinda Rizqa Aulia; Khairina Tambunan; Aqwa Naser Daulay (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study aims to examine and analyze the long-term and short-term impact of the trade balance on economic growth in North Sumatra. A quantitative approach using the Vector Error Correction Model (VECM) was employed to test the existence of both long-term and short-term relationships between export-import data and economic growth in North Sumatra. The study population includes all export-import and economic growth data published by the North Sumatra Central Bureau of Statistics (BPS), while the sample consists of quarterly data from 2012 to 2023, totaling 48 samples. The VECM analysis technique was implemented using EViews 10 software to estimate the model. The results show that in the long term, exports have a positive but insignificant effect on economic growth, while imports have no effect. In the short term, exports significantly influence economic growth, while imports do not. From an Islamic economic perspective, these findings suggest that trade balance policies have not yet achieved optimal results. Islamic economics emphasizes the importance of balance in trade for achieving broader societal well-being (maslahah). Therefore, the government should formulate more comprehensive policies that not only focus on increasing exports but also on product diversification, improving productivity, and enhancing human resource development to create a more sustainable and just economic environment